Effectiveness of prophylactic agents in prevention of oral mucositis in patients with head and neck cancer receiving radiotherapy - Al-Zahawi, Shukria M; Marouf, Showan S; Al-Barzenji, Hassan A M (Journal of Baghdad College of Dentistry, 2013)
Background: Oral mucositis is regarded as one of the major complications of radiation therapy especially in patients with head and neck cancer. The aim of this study was to evaluate the efficacy of glutamine in preventing or minimizing the development of mucositis of the oral cavity. Subjects and methods: Forty-six participants were randomly selected amongst those who were planned to receive radiation therapy for head and neck region cancers. They were randomly divided into two groups of 23 subjects, one group received glutamine and the second group received a placebo. Results: Glutamine had a statistically significant effect in reducing the occurrence and/or severity of oral mucositis in the treated patients compared to patients in the control group. Gender and age had no effect in the development or severity of oral mucositis in the studied patients. Conclusions: It can be concluded that glutamine can be used effectively to prevent or minimize oral mucositis amongst cancer patients who receive radiation therapy.